Achieving Negatively Charged Pt Single Atoms on Amorphous Ni(OH)2 Nanosheets with Promoted Hydrogen Absorption in Hydrogen Evolution - Liu, Yue; Liu, Gui; Chen, Xiangyu; Xue, Chuang; Sun, Mingke; Liu, Yifei; Kang, Jianxin; Sun, Xiujuan; Guo, Lin (Nano-Micro Letters, 2024)
Single-atom (SA) catalysts with nearly 100% atom utilization have been widely employed in electrolysis for decades, due to the outperforming catalytic activity and selectivity. However, most of the reported SA catalysts are fixed through the strong bonding between the dispersed single metallic atoms with nonmetallic atoms of the substrates, which greatly limits the controllable regulation of electrocatalytic activity of SA catalysts. In this work, Pt–Ni bonded Pt SA catalyst with adjustable electronic states was successfully constructed through a controllable electrochemical reduction on the coordination unsaturated amorphous Ni(OH)2 nanosheet arrays. Based on the X-ray absorption fine structure analysis and first-principles calculations, Pt SA was bonded with Ni sites of amorphous Ni(OH)2, rather than conventional O sites, resulting in negatively charged Ptδ−. In situ Raman spectroscopy revealed that the changed configuration and electronic states greatly enhanced absorbability for activated hydrogen atoms, which were the essential intermediate for alkaline hydrogen evolution reaction. The hydrogen spillover process was revealed from amorphous Ni(OH)2 that effectively cleave the H–O–H bond of H2O and produce H atom to the Pt SA sites, leading to a low overpotential of 48 mV in alkaline electrolyte at −1000 mA cm−2 mg−1Pt, evidently better than commercial Pt/C catalysts. This work provided new strategy for the controllable modulation of the local structure of SA catalysts and the systematic regulation of the electronic states. Highlights: 1 Pt–Ni bonded Pt single-atom (SA) catalyst, rather than classic Pt–O bonded SA catalyst, was successfully constructed. 2 The electronic states of Pt SA catalyst were deeply regulated and negatively charged Ptδ− was realized. 3 Pt–Ni bonded Pt SA catalyst-enhanced absorbability for activated hydrogen atoms and promoted hydrogen absorption.